Radical hemithorax radiotherapy induces an increase in circulating PD-1+ T lymphocytes and in the soluble levels of PD-L1 in malignant pleural mesothelioma patients: a possible synergy with PD-1/PD-L1 targeting treatment? - Revelant, Alberto; Gessoni, Francesca; Montico, Marcella; Dhibi, Raja; Brisotto, Giulia; Casarotto, Mariateresa; Zanchetta, Martina; Paduano, Veronica; Sperti, Filippo; Evangelista, Chiara; Giordari, Fabiana; De Re, Valli; et al. (Frontiers in Immunology, 2025)
Malignant Pleural Mesothelioma (MPM) is an aggressive tumor associated with asbestos exposure, characterized by a poor prognosis, managed with surgery, chemotherapy and radiotherapy. Recently, immunotherapy gives a survival advantage compared to chemotherapy, but limited to the non-epithelioid histotype, the rarest type. Radical hemithorax radiotherapy (RHRT) improves the Overall Survival (OS) of MPM patients, irrespective of histotype, and is able to induce immunomodulatory effects. In this study we aim to investigate changes in circulating T lymphocytes phenotype and activity, in MPM patients undergoing RHRT, to evaluate a possible therapeutic space for immunotherapy in this setting. To assess immunomodulatory effects of RHRT we evaluate peripheral blood samples of 35 MPM patients collected before treatment, at the end of RT, and 1 month later. We first notice that higher Lymphocyte-to-Monocyte Ratio (LMR) levels, before RT, are associated with an improved OS. The immune monitoring performed by ELISA assays reveals a significant increase in the serum levels of soluble PD-L1 (sPD-L1) and IFN‐γ at the end of RHRT. Furthermore, the percentage of PD‐1+ cells, evaluated by flow cytometry, significantly raise after RHRT in T cells, both CD4+ and CD8+. Also the proportion of proliferative cells is significantly expanded after RHRT in all T cell subtypes. After treatment we observe a significant increase in the number of patients showing WT-1 specific CD4+ T cells, measured by intracellular staining. The TCR repertoire analysis, investigated by Next Generation Sequencing, reveals an increased number of expanded T-cell clones after RHRT, and an association between TCR clonality and the percentage of proliferating cytotoxic T lymphocytes. The comparison of TCR sequences obtained in our cohort with those described in a literature cohort of MPM patients, reveals common entries, specific for MPM-associated antigens including WT-1. In this setting, pre-treatment levels of LMR seem to have a positive prognostic role, and RHRT would appear to induce immunomodulating effects, potential biomarkers for immunotherapy eligibility: i.e. increased PD-1+ T lymphocytes, proliferating T cells, expanded T cell clones and augmented levels of sPD-L1. These data suggest the design of a prospective study evaluating a maintenance immunotherapy after RHRT in MPM, even in the epithelioid histotype.